Connective management and governance network performance: the mediating role of throughput legitimacy. Findings from survey research on complex water projects in the Netherlands. (August 2015) - van Meerkerk, Ingmar; Edelenbos, Jurian; Klijn, Erik-Hans
In this paper we empirically examine the relationship between connective management, democratic legitimacy, and network performance in governance networks around complex water projects in the Netherlands. Realizing effective and legitimate solutions in such a context is highly challenging, as a variety of interests are at stake, and actors often disagree about goals of the water issue at stake. Although previous research has indicated the importance of network management for the performance of governance networks, the issue of democratic legitimacy is not much addressed in this relationship. Building on the literature, we expect to find that throughput legitimacy has a partly mediating role in the relationship between connective management and network performance. The results, based on survey research, indicate that governance networks have indeed democratic potential but, in order to make this potential manifest, network managers can play a key 'connective' role. Furthermore, the results confirm our hypotheses that throughput legitimacy positively affects network performance and that it has a mediating effect on the relationship between connective management and network performance. Network managers can create important conditions for the evolution of a democratic governance process, but are dependent on the way stakeholders interact with one another and the democratic quality of that interaction.